MOODS OF TURKİSH ADOLESCENTS İN HOME İSOLATİON DURİNG THE COVİD 19 PANDEMİC PROCESS - GÜNAY, Ulviye; COŞKUN ŞİMŞEK, Didem (Göbeklitepe Medical Science Journal, 2022)
To find out the effects of home confinement caused by novel coronavirus outbreak on adolescents. This study was conducted in Turkey between April and June 2020 with qualitative descriptive method. The participants are 40 adolescents who were studying at high school with ages ranging between 14 and 17. The data were collected through open-ended questions sent through e-mail. The adolescents stated that they were bored due to home confinement, they felt like in prison, distance learning was not efficient and that they missed their school and friends. In the content analysis conducted, the main themes of the study were (1) fear (fear of being transmitted with/transmitting coronavirus, fear of death), (2) deterioration in the education process (not being able to get efficiency from online lessons, getting into a holiday mood), (3) problems due to staying at home (mental problems, increase in social media use, decreased activity, (4) family relationships (increase in family relationships, conflict with family members), (5) longing (longing for school and friends, longing for pre-corona pandemic days). It was found that the pandemic caused by Covid 19 causes fear of being transmitted with/transmitting coronavirus and fear of death in adolescents.